Prediscourse Study on Identification of the Depth of Understanding Chemistry MGMP Teachers throughout Sidoarjo on Technology-Based Minimum Competency Assessment - Widarti, Hayuni Retno; Habiddin, Habiddin; Herunata, Herunata; Parlan, Parlan; Rokhim, Deni Ainur; Syafruddin, Afis Baghiz (Journal of Disruptive Learning Innovation (JODLI), 2023)
Understanding regarding the Minimum Competency Assessment has not been fully obtained by teachers. Teachers find it difficult to construct minimum competency assessment questions according to the criteria set in preparing for the National AKM. The purpose of this study was to find out how the level of depth of understanding of chemistry MGMP teachers in Sidoarjo regarding technology-based minimum competency assessment. Data collection techniques used in research are questionnaires, interviews, test questions, and documentation. The questions from the interview serve to explore the perspectives of AKM Teachers at MGMP Chemistry in Sidoarjo. The population formed as general student data related to AKM knowledge through Googleform. The results of the implementation of the open questionnaire on 15 MGMP chemistry teachers as a sample. The teacher's statement has represented the existing population. 75% of teachers strongly agree that it is necessary to prepare for AKM. In addition, 91.7% of teachers strongly agree and need teaching materials for AKM questions. As many as 91.7% of teachers strongly agree and need an application that facilitates the preparation of the National Assessment. Therefore, teachers really need intensive assistance in the preparation of the National Assessment, especially in abstract chemistry material.